2021
DOI: 10.1007/s10856-021-06556-0
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary hemocompatibility assessment of an innovative material for blood contacting surfaces

Abstract: Over the years, several devices have been created (and the development of many others is currently in progress) to be in permanent contact with blood: mechanical circulatory supports represent an example thereof. The hemocompatibility of these devices largely depends on the chemical composition of blood-contacting components. In the present work, an innovative material (hybrid membrane) is proposed to fabricate the inner surfaces of a pulsatile ventricular chamber: it has been obtained by coupling a synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Moreover, the favorable interaction between a material and the blood tissue is strongly contingent on composition, internal morphology, porosity, surface roughness and chemistry etc. [ 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the favorable interaction between a material and the blood tissue is strongly contingent on composition, internal morphology, porosity, surface roughness and chemistry etc. [ 44 , 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The hemocompatibility of these innovative materials was investigated by assessing their capacity to promote thrombin generation and induce platelet activation. Our preliminary results demonstrated that the proposed hybrid membranes are compatible with blood [131].…”
Section: Total Artificial Heart (Tah)mentioning
confidence: 65%
“…Recently, Todesco et al [135] combined decellularized pericardium with polycarbonate urethanes (Chronoflex AR and Chronoflex ARLT) to avoid the use of glutaraldehyde [26]. These two polymers are widely used in the biomedical field, particularly in cardiovascular applications, and their biocompatibility has already undergone extensive in vitro assessment [136].…”
Section: Hybrid Materials In the Cardiovascular Field: A Challenge Fo...mentioning
confidence: 99%